Portable Hardness tester for timber classification - Ballarin, Adriano Wagner [UNESP]; Almeida, Pedro; Palma, Hernando Lara [UNESP]; Colenci, Roberto (My University, 2010)
Hardness is a property largely used in material specifications, mechanical and metallurgical research and quality control of several materials. Specifically for timber, Janka hardness is a simple, quick and easy test, with good correlations with the compression parallel to grain strength, a strong reference in structural classification for this material. More recently, international studies have reported the use of Brinell hardness for timber assessment which resumes the advantages previously mentioned for Janka hardness and make it easier to be performed in the field, especially because of the lower magnitude of the involved loads. A first generation of an equipment for field evaluation of hardness in wood - Portable Hardness tester for wood - based on Brinell hardness has already been developed by the Research Group on Forest Products from FCA/UNESP, Brazil, with very good correlations between the evaluated hardness and several other mechanical properties of the material when performing tests with different species of native and reforested wood (traditionally used as ties - sleepers - in railways). This paper presents results obtained in the experimental program with the first generation of this equipment and preliminary tests with its second generation, which uses accelerometers to substitute the indentation measurements in wood. For the first generation of the equipment functional and calibration tests were carried out using 16 native and reforestation timber lots, among there E. citriodora, E. tereticornis, E. saligna, E. urophylla, E. grandis, Goupia glabra and Bagassa guianenses, with different origins and ages. The results obtained confirm its potential in the classification of specimens, with inclusion errors varying from 4.5% to 16.6%.
Keywords: Accelerometers; Brinell hardness; Janka hardness; Portable equipment; Sleepers; Timber; Calibration tests; Different origins; E. Tereticornis; Experimental program; Field evaluation; Forest products; Good correlations; Indentation measurements; Material specification; Parallel to grain; Research groups; Second generation; Structural classification; Equipment; Hardness testing; Reforestation; Software testing; Strength of materials; Hardness